Trynitarny aspekt creatio continua - Liszka, Piotr (Poznańskie Studia Teologiczne, 2016)
The act of creation on the part of God is unique, but it has a trinitarian shape, since it is contained in the internal life of God. The act of creation is the action of Divine Persons. It culminated in the world, created living and non-living, material and non-material beings. From the perspective of world history the act of creation may be looked upon as an act of God that brought about the existence of the world and also as God’s ongoing effort aimed at sustaining the world in its existence and constant bringing about new beings. Creation in general, including creatio continua, has a trinitarian shape. It is an act of three Divine Persons, and especially an act of the Son of God, who as the only one of the Trinity, has the ability to embrace our human condition. This ability found its reflection in the Incarnation. Being both God and man, Christ is not only an acting subject but also a personified Coming into existence.